Transesterification of diethyl oxalate with phenol over sol-gel MoO3/TiO2 catalysts - Kotbagi, Trupti; Duy Luan Nguyen; Lancelot, Christine; Lamonier, Carole; Thavornprasert, Kaew-Arpha; Zhu Wenli; Capron, Mickael; Jalowiecki-Duhamel, Louise; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dumeignil, Franck (Chemsuschem, 2012)
The transesterification of diethyl oxalate (DEO) with phenol to form diphenyl oxalate (DPO) has been carried out in the liquid phase over very efficient MoO3/TiO2 solid-acid solgel catalysts. A selectivity of 100?% with a remarkable maximum yield of 88?% were obtained, which opens the route to downstream phosgene-free processes for the synthesis of polycarbonates. Interpretation of the results of various acidity measurements (NH3 and pyridine desorption, methanol oxidation as a probe reaction) allowed us to identify the catalytic sites as Lewis acid sites.
Keywords: heterogeneous catalysis; Lewis acids; Oxidation; sol-gel processes; transesterification

Isolation, characterization, and identification of catalytically active species in the MoO3/SiO2 catalyst during solid acid catalyzed reactions - Kotbagi, Trupti V.; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Chemcatchem, 2013)
We report the isolation, characterization, and identification of the catalytically active species formed during various acid-catalyzed reactions if silica-supported MoO3 was used as a catalyst. We have reported previously the synthesis and extensive characterization of the silica-supported MoO3 catalyst prepared by the sol-gel process with ammonium heptamolybdate and ethyl silicate-40 as molybdenum and silica precursors, respectively. The TEM images showed uniformly distributed MoO3 nanoparticles on the high-surface area mesoporous silica support and high acidity (0.9mmolg-1) by using temperature-programmed desorption of ammonia (NH3-TPD) analysis. This catalyst has already shown high activity for various acid-catalyzed reactions. To understand the nature of catalytically active species formed during the reaction, the liquid-phase esterification of acetic acid and ethanol was studied as a probe reaction with very high acid conversion (83%) in 8h. During esterification, the reaction mixture turned blue, which indicated a change in the nature of the catalyst under reaction conditions. These catalytically active species formed in the reaction mixture were isolated and extensively characterized by using FTIR, Raman, powder XRD, BET surface area, NH3-TPD, energy dispersive X-ray, and TEM analysis. The characterization results revealed the insitu formation of silicomolybdic acid on the silica surface in the presence of water, which acts as catalytically active species responsible for the acid-catalyzed reactions.
Keywords: esterification reactions; heterogeneous catalysis; Molybdenum; silicon; sol-gel processes